PENGARUH KEPERCAYAAN DIRI SISWA BARU TERHADAP PENYESUAIAN DIRI DI SMPN 22 KOTA JAMBI - Windi Afriyani; Nelyahardi Gutji; Donny Rahmawaty (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Every individual experiences changes in the quality of self through the process, starting from small to large things. In the process of self-adjustment, students can face problems of acceptance and rejection in their relationships. Self-adjustment can be defined as the adaptation of the individual self to a new place in order to accept, such as students at school who must adapt to teachers, subjects, peers, and to the physical and social environment. Conditions such as self-confidence and limited abilities can make it difficult for students to adjust to a new school. The purpose of this study was to determine the level of self-confidence of new students, to determine the level of student self-adjustment, and to reveal the effect of new student self-confidence on student self-adjustment at SMPN 22 Jambi City, finding many seventh grade students who have difficulty adapting to a new environment and have problems adjusting to classmates, especially when studying. Type of quantitative research with an ex-post facto approach. The sampling technique used is simple random sampling with a confidence level of α 0.05 with the Slovin formula. The sample obtained was 153 students, which were divided into 9 classes. In the results of research calculations, seventh grade students at SMPN 22 Jambi City showed that their level of self-adjustment was at a “high” level with an overall percentage of 72.3%. The results showed that the new student self-confidence variable (X) had an influence on the self-adjustment variable (Y) of 6.3%. From the results of the questionnaire analysis on new student self-confidence and self-adjustment given to 153 seventh grade students at SMPN 22 Jambi City, it can be seen that there is an influence between new student self-confidence and self-adjustment, namely 6.3% which is at a “high or strong” level.